Strategi Kepala Sekolah untuk Meningkatkan Partisipasi Masyarakat dalam Pendidikan menuju Generasi Maju Indonesia - Wiwin Rif’atul Fauziyati (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2018)
Principal as a leader of educational institutions have a great role in information of advantage generation of smart, independent, and able to adaptin the life of global society. However, to achieve these things requires the participation of community in the implementation of educational programs atschool. Community involment in the management of education is an effort to community empowerement in the development of educational which meansengaging community in a planning, implementation and supervision of education. A various of principal strategies to increase communityparticipation are absolutely necessary. Among them through an effective communication relationship between school and community, communityinvolment and parents in school program, and empowerement of school comittees. Through various strategies are expected community participationwill be higher so that it will be able to realize the advanced generation of Indonesia.